Revisiting the use of art, imagery and symbolism in the Presbyterian Liturgical tradition in Korea : a practical-theological research - Lee, Keonsoo (Stellenbosch : Stellenbosch University, 2013., 2013)
Thesis (PhD)--Stellenbosch University, 2013.